2022
DOI: 10.3389/fendo.2022.947814
|View full text |Cite
|
Sign up to set email alerts
|

Dental health of pediatric patients with X-linked hypophosphatemia (XLH) after three years of burosumab therapy

Abstract: An inactivating PHEX gene mutation with the resultant accumulation of several mineralization-inhibiting proteins (e.g., FGF23) causes skeletal and dental morbidity in X-linked hypophosphatemia (XLH). This prospective case-control study explored the effect of burosumab, an anti-FGF23 antibody, on dental health of children with XLH. Ten children (age 4.3-15 years) with XLH underwent burosumab treatment per protocol. Assessment of their dental status at treatment initiation and after 1 and 3 years of treatment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…While information on the positive effects of burosumab on children's growth and biochemical profile has been accumulating since its introduction, there is a lack of data on its effects on dental health [58]. The effects on the potential prevention of periapical abscesses are particularly unclear [59].…”
Section: Discussionmentioning
confidence: 99%
“…While information on the positive effects of burosumab on children's growth and biochemical profile has been accumulating since its introduction, there is a lack of data on its effects on dental health [58]. The effects on the potential prevention of periapical abscesses are particularly unclear [59].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical, radiographic, and laboratory evaluations of dental status were performed during the initiation of Burosumab therapy and after one and three years. Enlarged pulp chambers persisted after treatment with Burosumab, as demonstrated by larger pulp-tocoronal height and width ratios in XLH patients than in healthy controls [57]. Dental abscesses were significantly decreased during treatment with Burosumab.…”
Section: The Impact Of Therapy On Dental Impairmentmentioning
confidence: 90%
“…A study by Kato et al supports the hypothesis that early treatment before the age of 5 years with phosphate supplements and vitamin D may have a preventive effect on dental complications [56]. Brener et al (2022) explored the effect of Burosumab on the dental health, dentition, and tooth morphology of ten children with XLH in a prospective case-control study [57]. They included children 8.8 ± 3.8 years old that who were diagnosed at a mean age of 1.9 ± 1.3 years and had been treated with conventional therapy for 7.0 ± 4.2 years [57].…”
Section: The Impact Of Therapy On Dental Impairmentmentioning
confidence: 91%
See 1 more Smart Citation
“…Data have shown that burosumab is more effective than conventional therapy in improving rickets, growth, lower limb deformity, and mobility in children with XLH ( 33 ). There is evidence that suggests that treatment with burosumab in children with XLH reduces the number of dental abscesses ( 25 , 34 ). However, further research is needed on the effects of burosumab on dental health in adult patients with XLH.…”
Section: Discussionmentioning
confidence: 99%